2017
DOI: 10.1063/1.4978408
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Si-B-P-C-Cu nanocrystalline soft magnetic powders with high B s and low core loss

Abstract: The magnetic properties of Fe-Si-B-P-C-Cu nanocrystalline powders were investigated. Fe-Si-B-P-C-Cu powders with a mostly amorphous structure were prepared by an atomization method. The atomized powders were annealed in inert gas atmosphere for nanocrystallization. The Fe84.8Si0.5B9.4P3.5C1Cu0.8 nanocrystalline powder exhibits high Bs of 1.76T, which is appreciably higher than that of conventional Fe-based amorphous powders (1.3 - 1.5 T) and close to that of Fe3.5Si4.5Cr (1.86T) crystalline one. The magnetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The specific values are shown in Table 1. It is found that the sphericity of the powders prepared by the SWAP method was worse than gas-atomized powders [10,12,17,18]. This difference is mainly due to the different surface tension and water jet interaction modes during the solidification of the smelt droplets in different preparation processes [17,18].…”
Section: Amorphous Forming Ability and Thermal Stability Of As-swaped...mentioning
confidence: 97%
See 1 more Smart Citation
“…The specific values are shown in Table 1. It is found that the sphericity of the powders prepared by the SWAP method was worse than gas-atomized powders [10,12,17,18]. This difference is mainly due to the different surface tension and water jet interaction modes during the solidification of the smelt droplets in different preparation processes [17,18].…”
Section: Amorphous Forming Ability and Thermal Stability Of As-swaped...mentioning
confidence: 97%
“…This could be caused by the heat transfer and heat accumulation inside the center [5,9,17,18]. The FIB-SEM images (Fig.…”
Section: Crystalline States and Soft Magnetic Properties Of As-swaped...mentioning
confidence: 99%
“…Soft magnetic materials have been attracting increasing attention as core products in various devices, such as communication equipment, power generation equipment, power conversion parts and electromagnetic wave shielding parts [1][2][3][4][5][6]. Recently, amorphous materials have also received considerable research attention because of their extremely low coercivity, high permeability and low core loss at a high frequency [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional method to cover this shortage is to increase the Fe content [5,6]. High Fe-content alloys like FeSiBPCu [7,8] and FeSiBPCuC [9,10] have been developed one after another. However, the H c of high Fe-content alloys increases rapidly during annealing at a low heating rate due to the rapid crystallization of α-Fe on pre-existing nuclei [11].…”
Section: Introductionmentioning
confidence: 99%